EFEITO DO CREEP FEEDING SOBRE O DESENVOLVIMENTO E COMPORTAMENTO ALIMENTAR DE BEZERROS NELORE E CRUZADOS NO PANTANAL - SILVA, Millena Vitória; CASTRO, Micheline Feitosa; HERNANDES, Maria Simara Palermo; GONÇALVES, Isabela Pinto; AMORIM, Lidianny dos Santos; OLIVEIRA, Dalton Mendes (ANAIS DO ENIC, 2022)
-